2014
DOI: 10.3109/03009742.2014.932432
|View full text |Cite
|
Sign up to set email alerts
|

Fear-avoidance beliefs about physical activity in adults with rheumatoid arthritis

Abstract: ObjectivesThe aim of this study was to describe fear-avoidance beliefs about physical activity and explore how these beliefs correlate with sociodemographic, disease-specific, and psychosocial factors in adults with rheumatoid arthritis (RA).MethodThis cross-sectional study is part of the Physical Activity in Rheumatoid Arthritis (PARA) 2010 study. The study participants (n = 2351) were identified through the Swedish Rheumatology Quality (SRQ) registries from six rheumatology clinics in Sweden. Univariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 41 publications
5
38
1
Order By: Relevance
“…In previous studies carried out in different disease groups, a correlation was put forth between level of pain and kinesiophobia (17)(18)(19). In another study conducted on patients with rheumatoid arthritis, it was concluded that the feelings of fear and avoidance of activity had a significant correlation with pain (20). Parallel to our results, as noted by Leeuwe et al, fear of pain, fear of movement, and fear of reinjury were frequently reported in diseases with pain components such as AS (21).…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies carried out in different disease groups, a correlation was put forth between level of pain and kinesiophobia (17)(18)(19). In another study conducted on patients with rheumatoid arthritis, it was concluded that the feelings of fear and avoidance of activity had a significant correlation with pain (20). Parallel to our results, as noted by Leeuwe et al, fear of pain, fear of movement, and fear of reinjury were frequently reported in diseases with pain components such as AS (21).…”
Section: Discussionmentioning
confidence: 97%
“…In RA, the role of fear‐avoidance and its development over time have been minimally explored and the few existing studies are inconclusive, reporting positive correlations with pain intensity but not with physical activity . RA is a long‐term condition, characterized by unpredictable flares and remissions with subsequent variations in pain, that also affects many other physical, psychological, and contextual aspects of health and functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, mFABQ total score was sum of these two scores. All scores dichotomized as low (mFABQ physical activity score [0-6], mFABQ work score [0][1][2][3][4][5][6][7][8][9][10][11][12] and mFABQ total score [0-18]) or high (mFABQ physical activity score [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], mFABQ work score and mFABQ total score ) according to medians of a previous study. 19 All patients were literate and none of the patients had pathological finding in the examinations that may influence the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Lööf et al 5 evaluated the FA beliefs about physical activity in adults with RA as a part of Physical Activity in Rheumatoid Arthritis 2010 study. Male sex, below average income, high level of pain, poor health and low health quality scores were found related with FA beliefs in RA.…”
mentioning
confidence: 99%
See 1 more Smart Citation